Pericardial effusion in children admitted with juvenile idiopathic arthritis: A multicenter retrospective cohort study from the pediatric health information system - Daniel Fiedorek; Xinyu Tang; Sukesh Sukumaran; R. Thomas Collins; Elijah Bolin (Archives of Rheumatology, 2023)
Objectives: This study aimed to determine if the presence of a pericardial effusion is associated with adverse outcomes among children admitted with juvenile idiopathic arthritis. Patients and methods: The multicenter, retrospective cohort study was conducted with 4,332 patients (1,554 males, 2,778 females; median age: 12 years; IQR, 7, 15 years) using the Pediatric Health Information System. Data from hospital admissions between January 1, 2004, and September 15, 2015, were obtained for patients with an International Disease Classification, Ninth Revision code for juvenile idiopathic arthritis. Pericardial effusion was the primary predictor variable; the outcomes of interest were length of stay, hospital costs, and readmission within 90 days. Multivariate models were created to evaluate associations between pericardial effusion and adverse outcomes. We also analyzed factors associated with increased odds of having pericardial effusion in juvenile idiopathic arthritis. Results: One hundred twenty (3%) patients had a code for pericardial effusion. Children with pericardial effusion had a longer median length of stay (7 days (IQR 3, 12) vs. 3 days (IQR 2,6), p<0.001), higher median costs (17,688 (IQR 8,657, 40,623) vs. 8,456 (IQR 4,865, 16,302), p<0.001), and greater rates of readmission (22% vs. 15%, p=0.045). Multivariate analysis demonstrated no significant association between pericardial effusion and outcomes of interest. Black race and male sex were associated with increased odds of having pericardial effusion. Conclusion: Pericardial effusion is rare among children admitted with juvenile idiopathic arthritis but is associated with significant morbidity; its presence may be a marker of disease severity. Black children and males admitted with juvenile idiopathic arthritis warrant special consideration and may benefit from screening echocardiography.